A system for stereotactic irradiation and magnetic resonance evaluations in the rat brain - Karger, Christian; Hartmann, Günther H.; Hoffmann, Ulf; Lorenz, Walter Josef (International journal of radiation oncology, biology, physics, 1995)
Purpose: A stereoactic fixation and localization device developed for small animal stereotactic radiosurgery is described. Methods and Materials: Irradiated volumes of spherical shape down to 1.7 mm in diameter at the 80% isodose level are attainable. The fixation device can also be used for magnetic resonance imaging (MRI) and allows target localization during magneitc resonance (MR) image content measurement. The capabilities of the entire system were investigated using a phantom that permitted measurement and localization of the three-dimensional dose distribution. Localization of target isocenter coordinates in MR images was also checked with the phantom. Results: An overall spatial error of about 1 mm for subsequent stereotactic irradiation was obtained. Conclusions: The accuracy of the fixation and localization techniques is adequate to investigate radiation-induced changes in the rat brain.
Elektronische Reproduktion der Druck-Ausgabe 23. Februar 2000
Gesehen am 29.07.2025